RANCANG BANGUN SISTEM INFORMASI PENGOLAHAN DATA ADMINISTRASI KEPENDUDUKAN BERBASIS WEB - Melani, Tyas; Sudarmilah, Endah (Ainet : Jurnal Informatika, 2024)
The population administration information system is an important part of a government agency where an order and arrangement is needed in the publication of a document and population data through civil registration, population registration services, management of population administration systems, utilization of results for services to the community. In the current era of technology, Jatiroto Village is still implementing a manual system of bookkeeping, this arrangement has an impact on the inefficiency and accuracy of population information. The purpose of this research is based on the main problems found in Jatiroto Village, namely to design a population administration data processing information system in which the system facilitates the management and archiving of documents so as to minimize paper usage. The method used for this research is the waterfall method where system development starts from requirements analysis, system design, implementation, integration and testing, maintenance. The system is expected to be able to meet the needs of Jatiroto Village in terms of data management and document reporting.